The Effect of E-Government-Based Public Service Innovation (M-Passport) And Employee Capability on Public Satisfaction Mediated By Trust - Cahyono, Puji (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
In Indonesia, public services, especially in passport issuance, are often highlighted due to various problems such as long queues, slow services, and unclear information. This study examines the relationship between public happiness and the overarching goals of employee competency and e-Government-based public service innovation (M-Passport) in relation to passport-making services at immigration offices, with trust serving as a mediating variable. The urgency of this research is to understand how service innovation and employee competency can enhance public satisfaction and trust in government services. The purpose of this research is to analyze the elements of public service innovation, employee capability, public satisfaction, and trust using quantitative methodologies with an associative approach. The research method involves data analysis using Partial Least Squares (PLS) with SmartPLS software version 3. The findings indicate that service innovation does not significantly impact trust, but it significantly increases public satisfaction. Employee capability does not significantly affect community satisfaction; however, it has a positive and significant effect on trust. Trust has a major impact on public happiness. The study concludes that service innovation and employee competency are crucial factors in enhancing public satisfaction and trust, particularly regarding passport-making services at immigration offices. These findings highlight the importance of trust in mediating the relationship between service innovation and public satisfaction, as well as the critical role of employee competency in strengthening public trust in government services.